Cost of a lymphedema treatment mandate: 10 years of experience in the Commonwealth of Virginia - Robert Weiss (Health Economics Review, 2016)
Treatment of chronic illness accounts for over 90 % of Medicare spending. Chronic lymphedema places over 3 million Americans at risk of recurrent cellulitis. Health insurers and legislators have taken an active role in fighting attempts to mandate the treatment of lymphedema for fear that provision of the physical therapy and compression materials would result in large and uncontrollable claim costs. The author knows of no open source of lymphedema treatment cost data based on population coverage or claims. Published studies compare cost of treatment versus cost of non-treatment for a select group of lymphedema patients. They do not provide the data necessary for insurance underwriters' estimations of expected claim costs for a larger general population with a range of severities, or for legislators' evaluations of the costs of proposed mandates to cover treatment of lymphedema according to current medical standards. These data are of interest to providers, advocates and legislators in Canada, Australia and England as well as the U.S. The Commonwealth of Virginia has had a lymphedema treatment mandate since 2004. Reported data for 2004-2013, representing 80 % of the Virginia healthcare insurance market, contains claims and utilization data and claims-based estimates of the premium impact of its lymphedema mandate. The average actual annual lymphedema claim cost was 1.59 per individual contract and 3.24 per group contract for the years reported, representing 0.053 and 0.089 % of average total claims. The estimated premium impact ranged 0.00-0.64 % of total average premium for all mandated coverage contracts. In this study actual costs are compared with pre-mandate state mandate commission estimates for proposed lymphedema mandates from Virginia, Massachusetts and California. Ten years of insurance experience with a lymphedema treatment mandate in Virginia shows that costs of lymphedema treatment are an insignificant part of insured healthcare costs, and that treatment of lymphedema may reduce costs of office visits and hospitalizations due to lymphedema and lymphedema-related cellulitis. Estimates based on more limited data overestimate these costs. Lymphedema treatment is a potent tool for reduction in healthcare costs while improving the quality of care for cancer survivors and others suffering with this chronic progressive condition.
Keywords: 330; Lymphedema treatment costs; Healthcare costs; Health insurance; Medical claims; Insurance mandates; Chronic disease management; Economic analysis; Treatment benefits